The Ezechiel’s Exagoge and its influence in the Byzantine tragedy. Text, translation and commentary (Circe de clásicos y modernos, 2018)
In the context of a study on the evolution of the tragic genre from the IV century B.C. to Byzantium, we stop in the Exagoge, the work of Ezechiel, in order to propose a text and a Spanish version (part 1); at the same time, in our commentary we emphasise the characteristics which make it to belong to this genre and its values as precedent of Byzantine plays (part 2).
Keywords: Byzantium; tragedy; Hellenism; Ezechiel; Exagoge